Guidance for Working Group Maintenance of the Systems Engineering Body of Knowledge (SEBoK) with Systems Security Engineering Example. Issue 1 (28th October 2015) - Mailloux, Logan O.; Garrison, Cheryl; Dove, Rick; Biondo, Ryan C.
Abstract: Recently the Systems Engineering Body of Knowledge (SEBoK) was established to facilitate the advancement of the systems engineering discipline, the maintenance of which has been accepted by the International Council on Systems Engineering (INCOSE) and others. Within INCOSE the responsibility to update and maintain the SEBoK is assigned to individual working groups with respect to their specialty areas. These working groups are populated with volunteers, each with limited participation timelines, special interests, and individual motivations. While SEBoK Editors have the responsibility to maintain a coherent evolution; they depend heavily on inputs from these maintenance groups and their subject matter experts. However, maintenance teams may have different views of what should be covered by the SEBoK than those in other periods, raising the possibility of cyclical focus‐thrash in topic areas, beyond the normal evolution of relevant topic information. Therefore, it is beneficial, and perhaps even necessary, for working groups to facilitate a cohesive approach for maintaining SEBoK content. In this paper, we provide guidance for working groups to maintain SEBoK materials based on the INCOSE systems security engineering working group's recent experiences.